Urbicide the City of Gaza - Ahmad Zaki Khalilia (Proceedings of the International Conference of Contemporary Affairs in Architecture and Urbanism-ICCAUA)
At 7 October Gaza city is being subjected to genocide as a result of the angry reaction, with most of the victims were children and women. South Africa submit a request to the International Court of Justice in a case entitled “Application of the Convention on the Prevention and Punishment of the Crime of Genocide in the Gaza Strip (South Africa v. Israel)”. Acceptance indicates the validity of the request. Urbicide the city is one of the methods used by the colonial authorities to redesign the urban environment, by demolishing homes, public buildings, infrastructure, hospitals, open spaces and even zoos, which would be a reformulation of the Palestinian narrative from the Israeli perspective. The study methodology is based on analyzing the Urbicide concept . which is done through understanding the phenomena, analyzing them, and comparing them with similar cases. This is done by analyzing some of the military objectives carried out during the war on urban, architectural, historical, governmental and community sites in Gaza. The place was destroyed, the population was dispersed, the features of the city changed, the infrastructure disappeared, and hope became a mere mirage. The extent of the interrelation between the urbicide and genocide is become clear.